Producción Científica en la Base de Datos Scopus de una Universidad Privada del Perú - Livia, José (2021)
Objective: to evaluate the scientific production of the Universidad de San Martin de Porres (USMP) between 1995-2020. Method: a bibliometric study was carried out, analyzing the articles published in Scopus database that registered the author’s affiliation with the USMP, analyzing the variables: number of publications, areas, authors, language, type of publication, journal, collaboration, and citations by article. Results: a total of 880 articles were located. There was an upward trend in the annual number of publications. Most of the articles (43.7%) belong to the medicine area, followed by social sciences (11%) and psychology (7.4%), the authors with the highest number of publications were: DomínguezLara, Merino-Soto, and Fujita, 61.3% of the articles are produced in English, 58.2% of the articles have at least one citation. Conclusion: there is evidence of an increase in scientific production, predominantly in the area of medicine and articles in English.